PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT DAN WORK ENGAGEMENT TERHADAP JOB PERFORMANCE PADA PERAWAT GENERASI Z DI RSIA JMB - Rica Yulianti Lukman; Nurul Fahmi Sultan; Rezky Ramadhani (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to determine whether the perception of organizational support and work engagement affect job performance in Gen z Nurses at RSIA JMB. This study was conducted on Gen z Nurses at RSIA JMB, using a purposive sampling method and the number of respondents was 30 respondents. The analysis techniques used were validity test, reliability test, classical assumption test and partial test (t). Based on the results of the hypothesis testing that has been carried out by the researcher, the conclusion is that the variable perceived organizational support (X1) does not have a significant effect on job performance (Y). While the variable work engagement (X2) has a significant effect on job performance (Y).